Genetic Engineering of Natural Killer Cells for Enhanced Antitumor Function - Mantesso, Simone; Geerts, Dirk; Spanholtz, Jan; Kučerová, Lucia (Frontiers in Immunology, 2020)
Natural Killer (NK) cells are unique immune cells capable of efficient killing of infected and transformed cells. Indeed, NK cell-based therapies induced response against hematological malignancies in the absence of adverse toxicity in clinical trials. Nevertheless, adoptive NK cell therapies are reported to have exhibited poor outcome against many solid tumors. This can be mainly attributed to limited infiltration of NK cells into solid tumors, downregulation of target antigens on the tumor cells, or suppression by the chemokines and secreted factors present within the tumor microenvironment. Several methods for genetic engineering of NK cells were established and consistently improved over the last decade, leading to the generation of novel NK cell products with enhanced anti-tumor activity and improved tumor homing. New generations of engineered NK cells are developed to better target refractory tumors and/or to overcome inhibitory tumor microenvironment. This review summarizes recent improvements in approaches to NK cell genetic engineering and strategies implemented to enhance NK cell effector functions.